1987
DOI: 10.1093/clinchem/33.4.604
|View full text |Cite
|
Sign up to set email alerts
|

Improved radioimmunoassay of melatonin in serum.

Abstract: Melatonin was extracted from serum by using Baker reversed-phase C-18 columns. More than 99% of the applied melatonin was retained by the columns, and more than 97% was eluted from the columns in 300 microL of methanol. We then determined melatonin in the serum extract by a modification of a standard radioimmunoassay, using filtration instead of centrifugation to collect the [3H]melatonin-antibody complex precipitated by saturated ammonium sulfate. These modifications allow more rapid, accurate, and reproducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Therefore, methods using systemic sampling cannot distinguish between tissue secretion sites, such as the salivary glands and pineal gland. Tissue speci city can be achieved by extracting samples from speci c tissues and then quantifying melatonin content with ELISA, radioimmunoassay (RIA), or electrochemical detection [26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, methods using systemic sampling cannot distinguish between tissue secretion sites, such as the salivary glands and pineal gland. Tissue speci city can be achieved by extracting samples from speci c tissues and then quantifying melatonin content with ELISA, radioimmunoassay (RIA), or electrochemical detection [26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, 2 ml of serum sample is passed through an LC-18 cartridge, which is then washed with 2 ml of water and 2 ml of water–methanol (90:10, v/v). Thereafter, melatonin can be eluted from the column with pure methanol, dried and resuspended in an appropriate solution for analysis [ 68 ] or can be further purified by eluting with 2 ml of water–methanol (40:60, v/v) and loading onto a Carbograph cartridge [ 31 ]. The cartridge is then washed with 10 ml of methanol and 3 ml of methanol–dichloromethane (80:20, v/v), and melatonin is finally eluted with 1.5 ml of methanol–dichloromethane (10:90, v/v).…”
Section: Introductionmentioning
confidence: 99%
“…Sieghart et al [ 68 ] reported that prior melatonin purification from plasma using reversed-phase column chromatography greatly reduces the problems of cross-reactivity. Moreover, Rolčik et al [ 74 ] used immunoaffinity chromatography employing specific antisera to process samples prior to HPLC-MS analysis.…”
Section: Introductionmentioning
confidence: 99%